2017
DOI: 10.3928/23258160-20170428-03
|View full text |Cite
|
Sign up to set email alerts
|

Three Different Optical Coherence Tomography Angiography Measurement Methods for Assessing Capillary Density Changes in Diabetic Retinopathy

Abstract: Only one of the three methods allowed for the detection of changes from the normal capillary density as early as at the "severe nonproliferative DR" stage due to several refinements from the basic technique. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:378-384.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Using this approach the combined model achieved a sensitivity of 86% and a specificity of 70% in the NPDR versus PDR group, compared to the previously reported sensitivity/specificity of 90%/44% for the SCP vessel density alone and 91%/50% for the DCP vessel density alone. 33 Furthermore, the same model performed well in the NoDR versus any DR group with a sensitivity of 89% and specificity of 96%, which compares favorably with previous attempts to differentiate normal eyes and eyes with DR, with the important difference that it is considerably harder to detect changes between NoDR and eyes with any DR. 5 , 34 …”
Section: Discussionsupporting
confidence: 66%
“…Using this approach the combined model achieved a sensitivity of 86% and a specificity of 70% in the NPDR versus PDR group, compared to the previously reported sensitivity/specificity of 90%/44% for the SCP vessel density alone and 91%/50% for the DCP vessel density alone. 33 Furthermore, the same model performed well in the NoDR versus any DR group with a sensitivity of 89% and specificity of 96%, which compares favorably with previous attempts to differentiate normal eyes and eyes with DR, with the important difference that it is considerably harder to detect changes between NoDR and eyes with any DR. 5 , 34 …”
Section: Discussionsupporting
confidence: 66%
“…Various vascular quantifications have been described including the area filled by binarized vessels (vessel area density = VD) or skeletonized vessels (vessel perfusion density = PD), vessel spacing or intercapillary area, length of the blood vessel based on the skeletonized OCTA (vascular length density = VLD or skeleton density = SD), vessel diameter index (VDI, calculated as VD divided by VLD), total length of vessels (vessel length fraction), vascular architecture, and branching [tortuosity and fractal dimension (FD)], and nonperfusion indexes (NPI). [ 12 17 19 34 44 64 65 66 ] To our knowledge, only VD indices and PD maps are available in some commercially available OCTA devices. SD, VD, FD, and VDI showed high reproducibility among graders.…”
Section: Resultsmentioning
confidence: 99%
“…Although the automated method may distinguish diabetic changes as early as severe NPDR, other methods can detect significant VD changes only in the more advanced stages of retinopathy (PDR). [ 65 ] Repeated VD measurements using the same device is reliable; however, significant variability exists in measurements using different devices and methods. [ 59 ] Hence, comparisons should be made using the same type of device.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study has provided some information about the impact of different post-processing imaging. Pedinielli et al [ 38 ] observed that the same image may lead to different macular vessel density values if quantified by means of skeletonization, mean thresholding, or proprietary AngioVue software (Optovue, Inc., Fremont, CA, USA). Differences between vessel density obtained by means of skeletonization and thresholding were predictable since they measure different units.…”
Section: Discussionmentioning
confidence: 99%